Indicators and metrics for social business: a review of current approaches. Issue 1 (2nd January 2016) - Irene, Bengo; Marika, Arena; Giovanni, Azzone; Mario, Calderini
Abstract: This paper aims to perform a review of different accounting frameworks, including indicators and metrics applicable to the social business sector, discussing the strengths and the weaknesses of different approaches in relationship to their ability to respond to objectives and interests of different stakeholders in the social business ecosystem. Then, the paper discusses the key role that indicators and metrics could play in the light of the transformations that the social business sector is witnessing, such as the emergence of new financial supply chains and the entrance of new relevant players.